2017
DOI: 10.3389/fcell.2017.00052
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cell Plasticity: Advantages in Therapy for the Injured Central Nervous System

Abstract: The physiological and pathological properties of the neural germinal stem cell niche have been well-studied in the past 30 years, mainly in animals and within given limits in humans, and knowledge is available for the cyto-architectonic structure, the cellular components, the timing of development and the energetic maintenance of the niche, as well as for the therapeutic potential and the cross talk between neural and immune cells. In recent years we have gained detailed understanding of the potentiality of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 339 publications
0
23
0
Order By: Relevance
“…Stem cells are very useful to reduce the complications of this disease. Studies showed that neural stem cells (NSCs) had a high potential for treatment of central nervous system disorders, such as cerebral ischemia (2). Methods of stem cells transplantation to the damaged tissue include intracerebral, intravenous and intra-arterial transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells are very useful to reduce the complications of this disease. Studies showed that neural stem cells (NSCs) had a high potential for treatment of central nervous system disorders, such as cerebral ischemia (2). Methods of stem cells transplantation to the damaged tissue include intracerebral, intravenous and intra-arterial transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Though the disconnect between in vitro and in vivo gene expression may at first suggest that only in vivo studies should be pursued, such a focused approach does not faithfully represent all biologically and therapeutically relevant stem cell sources. Current clinical trials use cultured neural stem cell lines while preclinical models use NSPCs with varying amounts of in vitro processing (Mazzini et al 2019;Ottoboni, Merlini, and Martino 2017;Mendes-Pinheiro et al 2018;Chandanala et al 2014). Thus, analysis of both cultured and acutely isolated stem cells is critical for the development of effective NSPC-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it was observed that these cells were able to extend multiple axons over long distances, and form synapses with host neurons ( 112 , 264 ). Research suggests that endogenous NSCs and the immune system share secreted mediators (chemokines, cytokines) and receptors relevant both to inflammation and the maintenance, structure, and function of endogenous neural stem cell niches in the brain ( 165 , 166 , 265 ). Transplanted exogenous NSCs may modulate local immune responses and secrete growth factors that are conducive to neuronal growth ( 132 , 133 ).…”
Section: Cell-based Approaches To Central Neural Repair and Regeneratmentioning
confidence: 99%